Evaluación de cuatro métodos para la extracción de microelementos en suelos del Valle del Cauca - García O., Alvaro; Crespo P., Carlos; Jiménez R., Diego (Instituto Colombiano Agropecuario, 2019)
To evaluate available micronutrients in soils from north and central areas of Cauca Valley, sampies of surface horizons of 30 soils were collected. Iron, Cu, Mn and Zn were extracted with: a) EDTA 0.01M + NaHCO3 0.5M; b) HCI 0.05N + H2SO4 0.025N; c) DTPA 0.05M, and d) HCI 0.1N. Available Boron (B) was extracted by using Ca (H2PO4)2 H20 0.008M; HCI 0.05N and NH4 OAc pH 4.8. To correlate the amount extracted from the soil with the amount taken up by the plants, tomato, sorghum and beans were planted in each soil. Microelements in tissue were determined by using nitric-perchioric acids mixture, and acid methanol digesting solutions for Fe, Mn, Cu and Zn. Total B in tissues was determined in ashes by Hunder's method. DTPA was advantageous to evaluate Fe and Cu in soils, HCI H2SO4 for Mn, EDTA + NaHA03 for Zn, and both Ca (H2 PO4 )2 H20 and HCI for B. The nitric-perchloric mixture correlated the best with the soil extracting solutions. Low to medium soil contents of B were detected for the area studied by using Ca (H2PO4 )2 H20 as extracting solution. The HCI + H2SO4 extracting solutions gave low contents of Cu in 16.7% of the soils analyzed, Zn deficiencies in 10% of the soils, and Fe in many of them. When Zn was determined using DTPA13.47o of soils were deficient, and only 10% when NaHCO3 + EDTA was used.